STUDY OF THE VALUE OF CULTURE AND LOCAL WISDOM IN THE INDIGENOUS PEOPLE OF TENGGER TRIBE - Sholahuddin Al-Fatih; Zakaria Saxon; Ahmad Murtadho (Universitas Muhammadiyah Tangerang, 2021)
The existence of indigenous peoples that are guaranteed directly in the constitution of the State of Indonesia. This research aims to analyze the value of culture and local wisdom, by the traditional and indigenous people, namely Tengger tribe. The type of legal research conducted is juridical empirical. The research will examine between the rule of law and the environment in which the law applies. This research found that Cultural values and local wisdom are one of the foundations of the existence of indigenous peoples. Because, through these values, indigenous peoples do all forms of law that they believe in and the system of life that has been agreed together to realize a regularity in the lives of indigenous peoples, especially indigenous peoples Tengger tribe.